Nursing Care for Septic Shock Patients Using Indonesian Nursing Standards: A Case Reports - Sugiharto, Firman; Rahmi Harlasgunawan , Alia; Sesilia , Fitri; Heriyansyah, Heriyansyah; Dos Reis , Silvestre; Anna , Anastasia (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This case report aimed to identify gaps in applying the Nursing Standard Guidelines of the Indonesian Association in critical care, specifically focusing on patients with septic shock. Methods: This study used a case report with a nursing care approach that includes an assessment to evaluation. Nursing care was provided to a patient who was experiencing septic shock, was on a ventilator, and had experienced organ failure. Results: A 63-year-old man on mechanical ventilator was diagnosed with septic shock caused by community-acquired pneumonia. The nursing diagnoses for this case included impaired spontaneous ventilation related to respiratory muscle weakness, ineffective airway clearance related to the accumulation of secretions, peripheral tissue perfusion disorders related to changes in fluid regulation, and risk of infection. The study identified inappropriate nursing diagnoses, such as 'impaired spontaneous ventilation for patients on mechanical ventilation. Conclusion: This study concludes that there are still several gaps in diagnosing and managing clinical conditions in critical cases. The nursing problem of impaired spontaneous ventilation should not have been identified as the patient was already on a ventilator. Additionally, there was no actual diagnosis for impaired organ perfusion or infection. This case report recommends further developing the Nursing Standard Guidelines of the Indonesian Nursing Association to optimize coverage of critical care. Recommendations include revising the Indonesian Nursing Diagnosis Standards to align with critical care needs. This enhancement will help nurses and clinicians in critical care not experience confusion when applying the current guidelines.